Accurate experimental determination of rock fracture toughness under simulated reservoir confining pressures. (August 2022) - Antinao Fuentealba, Fabián J.; Bianchi, Leandro N.; Otegui, José L.; Bianchi, Gustavo L.
Highlights: A novel LEFM method to assess KIC  in Round Bar Straight-Notch samples of shale rocks subjected to confining pressure has been developed. A primary chamber induces a fluid-driven Mode-I opening, a secondary chamber ensures variable hydraulic confinement up to 80 MPa. Experimental and finite element modelling results validated equations and quantified all possible sources of experimental biases. Effects of confinement on KIC  in terms of crack closure mechanisms are recognized as a cause for increased toughness as confinement rises. Abstract: Rock toughness under confining pressure is recognized as a key mechanical property to understand brittle fracture in oil and gas projects. This article discusses a linear elastic fracture mechanics method to assess the critical stress intensity factor (KIC ) of shale rocks subjected to confining pressure. Linear elastic fracture toughness (KIC ) is determined in Round Bar Straight-Notch (RBSN) samples by a novel experimental set up. The device uses a primary chamber to apply a fluid-driven load to induce Mode-I opening. A secondary and independent chamber ensures variable hydraulic confinement pressures, up to 80 MPa, and both systems are isolated by O-rings. This allows analyzing the influence of fluid composition, temperature and confinement pressure. Early testing and finite element modelling allowed validating experimental results and identifying possible sources of experimental errors. Experimental assessment is discussed in terms of KIC tests. The effects of confinement on KIC in terms of crack closure mechanisms are recognized, pointing out a plausible cause for increased toughness as confinement rises.